FOOD SECURITY IN SUDAN: A HISTORICAL ANALYSIS OF FOOD AVAILABILITY - & Ahmed, Elbushra (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
This study aimed to analyse historical food availability in Sudan during 1961-2013. This was achieved by assessing the food supply (kg/capita/yr.), dietary energy supply (DES) (kcal/capita/day), composition of diets and food self-sufficiency. The study depended on the available secondary data from FAO balance sheets. Percent share, annual cumulative growth rate and trends were used as analytical tools. The total food supply had a positive growth rate of 4.9%. The DES increased from 1743 to 2186 kcal/capita/day, implying that Sudan is food insecure. Cereals constitute approximately half of the total DES. The percentage share of vegetal sources was paramount in the DES (80%), protein supply (60%) and fat supply (45-68%) relative to that of animal sources. The per capita consumption of protein and fat (g/capita/day) were considered within the adequate supply, and below the average of the world and Arab countries. Carbohydrates ranked as the highest source contributing to the DES, followed by fats and proteins. These macro-nutrient contributions to the total DES fell within the recommendation ranges of the WHO for the balanced diets. The growth rate of imports outnumbered that of the domestic food supply and production, reflected in declining trend of the overall food self-sufficiency ratio by 1.5% per decade. The study recommended efficient use of Sudan abundant resources to increase food availability.